Lack of knowledge and false perception on space spraying against dengue in endemic area - Siwi Pramatama Mars Wijayanti; Devi Octaviana; Arnika Dwi Asti (International Journal of Public Health Science (IJPHS), 2020)
Space spraying is still considered as the most powerful method to control the spread of dengue virus transmission, particularly in an emergency such as an outbreak. However, there is still limited information about how the knowledge and perception of people about space spraying against dengue. This study aimed to assess knowledge and community perception of space spraying against dengue in an endemic area. This study was a descriptive cross-sectional study, involved 273 respondents in three endemic areas in Kebumen Regency, Central Java, Indonesia. Structured questionnaires about knowledge and perception of space spraying were administered to the respondents. The 41.4% of respondents had poor knowledge about space spraying, and 42.1% had a negative perspective about space spaying. Only 15.4 % of respondents aware that space spraying applications must be carried out based on several criteria and procedures. Most of them assumed that space spraying can be applied anytime and feel secure when space spraying was applied in their near area. Lack of knowledge and false security on space spraying applications could make people less active to conduct routine practice of mosquito breeding site eradication. It is important to enhance community knowledge and perception of space spraying, so they could understand that space spraying application only for emergencies and routine mosquito breeding site prevention must be carried out regularly.